2012
DOI: 10.1590/s1516-35982012000800007
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies and intensities of defoliation in Aruana guineagrass swards: morphogenetic and structural characteristics

Abstract: -The objective of this study was to evaluate the morphogenetic and structural characteristics of Aruana influenced by the frequency and intensity of grazing adopted, as well as by the seasons, implying that the capacity and speed for the recovery of Aruana grass pastures after grazing depend mainly on the management and edaphoclimatic conditions. The best grazing management for Aruana guineagrass is 95% canopy light interception, i.e., 30 cm pre-grazing height pastures interrupted when reaching 15 cm residue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
8

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 27 publications
0
20
0
8
Order By: Relevance
“…In addition, long grazing intervals characterized by the pre-grazing target of LImax result in a greater proportion of the produced herbage being lost to the soil as a consequence of physical damage and/or rejection, decreasing the efficiency of the grazing process [85,90,91]. The investment in stem elongation results in taller swards with an increased proportion of stems in the upper layers of their vertical profile [92], increasing the difficulty of grazing and in maintaining the post-grazing management targets [93,94]. As a result, the benefit of greater total herbage accumulation is offset by the greater grazing losses when long regrowth intervals are used, indicating that, although herbage accumulation per grazing cycle is smaller when managing with shorter grazing intervals (LI95%), the more frequent defoliation results in larger number of grazing cycles and total herbage accumulation (with higher leaf proportion) than when managing with longer grazing intervals (LImax) [84,91,94,95].…”
Section: Morphological Plant Types and Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, long grazing intervals characterized by the pre-grazing target of LImax result in a greater proportion of the produced herbage being lost to the soil as a consequence of physical damage and/or rejection, decreasing the efficiency of the grazing process [85,90,91]. The investment in stem elongation results in taller swards with an increased proportion of stems in the upper layers of their vertical profile [92], increasing the difficulty of grazing and in maintaining the post-grazing management targets [93,94]. As a result, the benefit of greater total herbage accumulation is offset by the greater grazing losses when long regrowth intervals are used, indicating that, although herbage accumulation per grazing cycle is smaller when managing with shorter grazing intervals (LI95%), the more frequent defoliation results in larger number of grazing cycles and total herbage accumulation (with higher leaf proportion) than when managing with longer grazing intervals (LImax) [84,91,94,95].…”
Section: Morphological Plant Types and Growthmentioning
confidence: 99%
“…Marandu) [101], Panicum maximum cv. Aruana [93], and Pennisetum purpureum cv. Napier [94,95], showing consistency within a wide range of morphological types and a strong light effect determining plant growth.…”
Section: Morphological Plant Types and Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Under rotational grazing, recent studies focused on tropical grasses have shown that light interception (LI) is the best criteria to determine ideal grazing events, during regrowth (Barbosa et al, 2007;Carnevalli et al, 2006;Zanini, Santos, & Sbrissia, 2012). Optimal net forage accumulation (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Particularmente, sob pastejo rotativo, estudos recentes realizados com gramíneas tropicais (CARNEVALLI et al, 2006;BARBOSA et al, 2007;ZANINI;SBRISSIA, 2012) apontaram a interceptação luminosa durante a rebrotação como critério adequado para definição do ponto ideal para realização do pastejo. Adicionalmente, foi demonstrada a importância de se definir a altura de saída dos animais dos pastos, uma vez que esta se relaciona diretamente com o consumo de forragem e a ingestão de nutrientes pelos animais (CARVALHO et al, 2009), perdas e eficiência de pastejo (CARNEVALLI et al, 2006;SILVEIRA et al, 2013) e velocidade de rebrotação (DA SILVA et al, 2009).…”
Section: Introductionunclassified